Crystal plasticity modeling of damage accumulation in dissimilar Mg alloy bi-crystals under high-cycle fatigue. (September 2016) - Knight, Simon; Diak, Bradley J.; Daymond, Mark R.
Highlights: A CPFEM predicts the slip/twinning systems observed in Mg single crystal deformation. Polycrystalline fatigue is simplified into a bi-crystal scheme. Bi-crystals are used to identify possible bad orientation combinations for fatigue. For the first time a CPFEM describes the HCF behavior of Mg AZ31-AZ80 bi-crystals. The accumulated plastic shear strain is defined as a possible measure of damage. Fatigue performance declines with basal slip or twinning, and is neighbor dependent. Abstract: Damage accumulation in Mg AZ31–AZ80 alloy bi-crystals under fatigue loading at room temperature is studied using a modified version of the crystal plasticity finite element model of Abdolvand and Daymond. The model accounts for strain accommodation by both slip and tensile twinning, and is first shown to reasonably describe monotonic single crystal Mg experimental data from the literature. The high cycle fatigue behavior was then investigated in misoriented dissimilar alloy bi-crystals through stress-controlled simulations up to 1000 cycles. Nine different orientation combinations were simulated and the fatigue damage evolution, defined as the cumulative shear strain amplitude, were compared and analyzed. The bi-crystal geometry was used to simulate possible microstructure combinations occurring, for instance within an idealized friction stir weld. Findings suggest that when either of the alloy bi-crystal grains is oriented for basal slip, poor fatigue performance can occur by twinning or slip localization depending upon the neighboring orientation.